Cost Analysis in Helicobacter pylori Eradication Therapy Based on a Database of Health Insurance Claims in Japan - Tokunaga K; Suzuki C; Hasegawa M; Fujimori I (Dove Medical Press, 2021)
Kengo Tokunaga 1Chihiro Suzuki 2Miyuki Hasegawa 2Ikuo Fujimori 21Department of General Medicine, Kyorin University School of Medicine, Tokyo, Japan; 2Japan Medical Office, Takeda Pharmaceutical Company Limited, Tokyo, Japan   Correspondence: Kengo TokunagaDepartment of General Medicine, Kyorin University School of Medicine, 6-20-2 Shinkawa, Mitaka-Shi, Tokyo, 181-8611, JapanTel +81-422-47-5511Email kentoku@ks.kyorin-u.ac.jp   Objective: Cost-benefit is an important consideration for Helicobacter pylori (H. pylori) eradication in Japan, where 1.5 million patients were reported to receive first-line eradication annually. This study aimed to identify the optimal cost-saving triple therapy regimen for H. pylori eradication in Japan.Materials and Methods: This retrospective observational study used data from a largescale, nationwide health insurance claims database (2015‒2018). Using success rates of first-line eradication, mean total costs of first-line and second-line eradications per patient were compared between regimens including a potassium-competitive acid blocker (P-CAB) or a proton pump inhibitor (PPI), and between two clarithromycin  (CAM) doses (400 and 800 mg/day). Subgroup analyses by smoking habit or body mass index (BMI) were performed.Results: Among propensity score (age, gender, CAM dose, disease name)-matched patients (P-CAB regimen, n=22,002; PPI regimen, n=22,002), total costs were lower with the P-CAB than the PPI regimen (Japanese yen [JPY] 12,952 vs 13,146) owing to significantly higher first-line eradication rates with the P-CAB regimen (93.6% vs 79.7%; p<0.001). For both regimens, even among current smokers or patients with BMI ≥25 kg/m2, eradication rates did not differ by CAM dose, and total costs were approximately JPY1000 lower with CAM 400 mg/day than with CAM 800 mg/day.Conclusion: High success rate of first-line eradication contributes to saving in total eradication costs by reducing costs of subsequent therapy, irrespective of patients’ smoking status or BMI class. The combination of more potent acid-inhibitory medicine and low-dose CAM may be the optimal regimen in terms of efficacy and cost-benefit in Japan. Keywords: Japanese claims database, cost analysis, potassium-competitive acid blocker, Helicobacter pylori eradication, clarithromycin-dose, health resource